Mongol : [videorecording (DVD)] : the rise of Genghis Khan - Bodrov, Sergeĭ, 1948-; Asano, Tadanobu; Sun, Honglei; Chuluun, Khulan, 1985- (New Line Home Entertainment, 2008)
Delves into the dramatic and harrowing early years of the ruler who was born as Temudgin in 1162. Follows Temudgin from his perilous childhood to the battle that sealed his destiny. Shows the future conqueror and revealing him not as the evil brute, but as an inspiring, fearless and visionary leader.